A low-temperature co-precipitation approach to synthesize fluoride phosphors K2MF6:Mn4+ (M = Ge, Si) for white LED applications1. Issue 8 (28th February 2015) - Wei, Ling-Ling; Lin, Chun Che; Fang, Mu-Huai; Brik, Mikhail G.; Hu, Shu-Fen; Jiao, Huan; Liu, Ru-Shi
<x xml:space="preserve">Abstract</x> A new class of Mn4+ activated alkali-metal hexafluoride red phosphors are emerging for white light-emitting diodes because of their sharp red line 2Eg → 4A2g emissions (600–650 nm) excited by irradiation of 4A2g → 4T1g (320–380 nm) and 4A2g → 4T2g (380–500 nm) transitions.